A Visible‐Light Harvesting System for CO2 Reduction Using a RuII–ReI Photocatalyst Adsorbed in Mesoporous Organosilica. Issue 3 (18th December 2014) - Ueda, Yutaro; Takeda, Hiroyuki; Yui, Tatsuto; Koike, Kazuhide; Goto, Yasutomo; Inagaki, Shinji; Ishitani, Osamu
Abstract A photocatalytic system for CO2 reduction exhibiting visible‐light harvesting was developed by preparing a hybrid consisting of a supramolecular metal complex as photocatalyst and periodic mesoporous organosilica (PMO) as light harvester. A RuIIReI binuclear complex (RuRe) with methylphosphonic acid anchor groups was adsorbed on acridone or methylacridone embedded in the walls of PMO mesochannels to yield the hybrid structure. The embedded organic groups absorbed visible light, and the excitation energy was funneled to the Ru units. The energy accumulation was followed by electron transfer and catalytic reduction of CO2 to CO on the Re unit. The light harvesting of these hybrids enhanced the photocatalytic CO evolution rate by a factor of up to ten compared with that of RuRe adsorbed on mesoporous silica without a light harvester.